A three-dimensional modelling of the layered structure of comet 67P/Churyumov-Gerasimenko. (13th November 2017) - Penasa, L; Massironi, M; Naletto, G; Simioni, E; Ferrari, S; Pajola, M; Lucchetti, A; Preusker, F; Scholten, F; Jorda, L; Gaskell, R; Ferri, F; et al.
Abstract: We provide a three-dimensional model of the inner layered structure of comet 67P based on the hypothesis of an extended layering independently wrapping each lobe. A large set of terrace orientations was collected on the latest shape model and then used as a proxy for the local orientation of the surfaces of discontinuity which defines the layers. We modelled the terraces as a family of concentric ellipsoidal shells with fixed axis ratios, producing a model that is completely defined by just eight free parameters. Each lobe of 67P has been modelled independently, and the two sets of parameters have been estimated by means of non-linear optimization of the measured terrace orientations. The proposed model is able to predict the orientation of terraces, the elongation of cliffs, the linear traces observed in the Wosret and Hathor regions and the peculiar alignment of boulder-like features which has been observed in the Hapi region, which appears to be related to the inner layering of the big lobe. Our analysis allowed us to identify a plane of junction between the two lobes, further confirming the independent nature of the lobes. Our layering models differ from the best-fitting topographic ellipsoids of the surface, demonstrating that the terraces are aligned to an internal structure of discontinuities, which is unevenly exposed on the surface, suggesting a complex history of localized material removal from the nucleus.